PERANCANGAN SISTEM INFORMASI E- ABSENSI PEGAWAI PADA DRIVING RANGE GOLF MATOA JAKARTA SELATAN MENGGUNAKAN QRCODE BERBASIS WEBSITE - Rizki Rafly Rahmawan (2021)
Technology at this time has begun to develop very rapidly. Lots of tools have been found to facilitate human work, one of them is a quick response code (QR code). QR code is a matrix code or two-dimensional barcode created to make it easier for scanners to respond quickly and receive data quickly. QR codes can be used for managing employee attendance at a company. QR code can be used to assist the process of managing data in the database. In this case, employees at the Driving Range Golf Matoa, South Jakarta, still use the manual attendance method, which method is very outdated or can be said to be technologically behind, because with manual absences like that, employees can make fraudulent actions or manipulate the absence. Therefore the right method to minimize this is employee attendance using a QR code. The main component of this system is the smartphone camera as a scanner to read the provided QR code. The QR code provided on the personal computer will continue to change every second to further minimize manipulation, and the personal computer (PC) to run this application system is designed with the hypertext preprocessor (PHP) programming language with the codeigniter framework and MySQL for database creation. The results of the test, the application system carried out by the admin through the blackbox method has successfully run according to the initial plan, which is to help the attendance process to be more effective and efficient and the smartphone camera can read the QR code that has been provided accurately. The process of inputting data into the database can run well according to the design.